Macroscopic homochiral helicoids self-assembled via screw dislocations - Wu, Shengfu; Song, Xin; Du, Cong; Liu, Minghua (Nature communications, 2024)
Chirality is a fundamental property in nature and is widely observed at hierarchical scales from subatomic, molecular, supramolecular to macroscopic and even galaxy. However, the transmission of chirality across different length scales and the expression of homochiral nano/microstructures remain challenging. Herein, we report the formation of macroscopic homochiral helicoids with ten micrometers from enantiomeric pyromellitic diimide-based molecular triangle (PMDI-Δ) and achiral pyrene via a screw dislocation-driven co-self-assembly. Chiral transfer and expression from molecular and supramolecular levels, to the macroscopic helicoids, is continuous and follows the molecular chirality of PMDI-Δ. Furthermore, the screw dislocation and chirality transfer lead to a unidirectional curvature of the helicoids, which exhibit excellent circularly polarized luminescence with large | g lum | values up to 0.05. Our results demonstrate the formation of a homochiral macroscopic organic helicoid and function emergence from small molecules via screw dislocations, which deepens our understanding of chiral transfer and expression across different length scales. Chirality is observed at hierarchical scales from subatomic to macroscopic but the transmission of chirality across different length scales and the expression of homochiral nano/microstructures remain challenging. Here, the authors report the formation of macroscopic homochiral helicoids via a screw dislocation-driven co-self-assembly.